100 How accurate are argentine main on-line newspapers when they inform about breast cancer screening? cross-sectional study. (20th August 2018) - Spina, Silvia; Lombardi, Vanina; Terrasa, Sergio; Villalón, Gabriel; Kopitowski, Karin
Abstract : Introduction: Mass media have a key role in the communication of breast cancer screening strategy to the population. Misinformation and erroneous information, as well as the spreading of medical publications that are outdated or fail to be supported by any scientific evidence, serve as a barrier and prevent the implementation of adequate preventive practices from being carried out by the population. In furtherance of its early detection, the National Cancer Institute of Argentina ('Instituto Nacional del Cáncer de Argentina' -INC-, by its Spanish acronym), an agency of the Argentine Ministry of Health, following the recommendations issued by the U.S. Preventive Services Task Force (2016) and the Canadian Task Force on Preventive Health Care (2011), recommends healthy women to have a mammography once every two years after they turn 50, until they turn 70 years old. Objectives: To document the agreement between the breast cancer prevention information published on the Internet sites of the main Argentine newspapers and the INC recommendations. To describe and quantify the main messages that fail to agree with the recommendations of the INC. Method: Design: A cross-sectional documentary study was carried out. Context: Two researchers looked for news articles related to breast cancer that were published between 01/Jan/2015 and 31/Dec/2015, on the websites of the five newspapers with the most digital traffic in the country - Clarín, Infobae, La Nación, Página/12 and Perfil . Inclusion criteria: Digital content promoting secondary preventive strategies for breast cancer in women. Variables: Two independent researchers determined whether such contents had information which followed the recommendations of the INC regarding secondary preventive strategies for breast cancer. Whenever there was disagreement between them, a third researcher studied the disagreeing contents, not knowing the findings of the other two researchers. All contents which recommended healthy women between 50 and 70 years old (with no personal or family breast cancer history) to have a mammography every two years were considered concordant with the recommendations of the INC. Results: 135 news articles were identified, 95 of them were excluded because they failed to meet the inclusion criteria. 40 articles were included in the analysis. 95% of them (38/40) disagree with the INC recommendations on breast cancer screening in low risk general population (with no personal or family breast cancer history). Among the recommendations which failed to agree with those of the INC, the most frequently identified (33/40; 82.5%) was the one related to having a mammography once a year after turning 40; followed by the ones related to the promotion of periodical breast self-examinations (20/40; 50%) and the promotion of other periodical tests, such as breast scans or magnetic resonance imaging (6/40; 15%). Conclusions: During the term under analysis, the mass media, which can create and consolidate conducts, beliefs and values in the population, as well as provide information that is taken into consideration for health-related decisions, provided incomplete, confusing information which failed to agree with the recommendations made by the INC. This may probably result in the population being confused and in the demand for studies, such as mammographies, being performed at younger ages or at inappropriate intervals, with all the risks involved. In order to prevent or minimize the damage caused by health activities, it is necessary to make current scientifically supported recommendations on this issue even more visible, which will help dispel erroneous beliefs in relation to breast cancer and clarify information on the benefits, risks, and effectiveness of the different breast cancer tests, thus improving health outcomes, and at the same time minimizing harm and unnecessary interventions.